Impact of Kisan Credit Card Scheme on Agriculture Production: A Case Study of Kathua District - Andotra, Neetu; Gupta, Pooja (International Journal of Economic Plants, 2015)
Present study was conducted to measure the before and after effects of KCC usage on agriculture production. Census method was used in collecting primary data. Self-structured schedules were used to elicit information from 252 KCC holders during the months of August to November, 2014. Findings revealed that with the introduction of KCC usage, the average yields (q ha-1) of wheat, paddy, maize, blackgram, vegetable crops and mustard were increased when compared to the yields realized before the usage of KCC, initiation of pre-sowing & post-sowing activities, more of the land was getting irrigated and qualitative progress was seen in the usage of agricultural inputs.The study is restricted to Hiranagar zone only, bank managers of the area were found to be hesitant in sharing factual financial and detailed information of KCC holders, the respondents seem to be unwilling due to lack of interest, negligence and communication problem. The element of subjectivity in interpretation cannot be ruled out in eliciting requisite information.